Influence of non-allergenic fining agents on white wine phenolic and volatile composition - Quintela, Jorgina (2018)
White wine fining is important to stabilize wine colour by removing phenolic compounds. The choice of oenological products is important since consumers are concerned regarding food safety. Due to allergic reaction problems by some consumers, together with the restriction of EU legislation [1], non-allergenic fining agents are being developed in detriment of traditionally used. However, the impact these fining agents on wine phenolic and volatile compounds are not well known. This work aims to evaluate the impact of six fining agents (one traditionally used potassium caseinate and five non-allergens) on wine phenolic and volatile compounds as well as on the sensory profile of a white wine from the Douro Region. All non-allergenic fining agents tested prevent the browning capacity. This could be related to the decrease in white wine colour observed. Sensory analysis indicated that only the wines treated with potassium caseinate and polyvinylpolypyrrolidone showed a significant decrease in colour attribute.